Catechol-O-Methyltransferase (COMT) Val108/158 Met polymorphism does not modulate executive function in children with ADHD - Stepanian Marina; Torkaman-Zehi Adam; Deguzman Rosherie; Mbekou Valentin; Lageix Philippe; Amor Leila; Grizenko Natalie; Taerk Evan; Baron Chantal; Joober Ridha (BMC, 2004)
Abstract Background An association has been observed between the catechol-O-methyltransferase (COMT) gene, the predominant means of catecholamine catabolism within the prefrontal cortex (PFC), and neuropsychological task performance in healthy and schizophrenic adults. Since several of the cognitive functions typically deficient in children with Attention Deficit Hyperactivity Disorder (ADHD) are mediated by prefrontal dopamine (DA) mechanisms, we investigated the relationship between a functional polymorphism of the COMT gene and neuropsychological task performance in these children. Methods The Val108/158 Met polymorphism of the COMT gene was genotyped in 118 children with ADHD (DSM-IV). The Wisconsin Card Sorting Test (WCST), Tower of London (TOL), and Self-Ordered Pointing Task (SOPT) were employed to evaluate executive functions. Neuropsychological task performance was compared across genotype groups using analysis of variance. Results ADHD children with the Val/Val, Val/Met and Met/Met genotypes were similar with regard to demographic and clinical characteristics. No genotype effects were observed for WCST standardized perseverative error scores [F2,97 = 0.67; p > 0.05], TOL standardized scores [F2,99 = 0.97; p > 0.05], and SOPT error scores [F2,108 = 0.62; p > 0.05]. Conclusions Contrary to the observed association between WCST performance and the Val108/158 Met polymorphism of the COMT gene in both healthy and schizophrenic adults, this polymorphism does not appear to modulate executive functions in children with ADHD.